BMP-4 Genetic Variants and Protein Expression Are Associated with Platinum-Based Chemotherapy Response and Prognosis in NSCLC. (19th March 2014) - Xian, Sun; Jilu, Lang; Zhennan, Tian; Yang, Zhou; Yang, Hu; Jingshu, Geng; Songbin, Fu
Abstract : To explore the role of genetic polymorphisms of bone morphogenic proteins 4 (BMP-4) in the response to platinum-based chemotherapy and the clinical outcome in patients with advanced nonsmall cell lung cancer (NSCLC), 938 patients with stage III (A+B) or IV NSCLC were enrolled in this study. We found that the variant genotypes of 6007C > T polymorphisms significantly associated with the chemotherapy response. The 6007CC genotype carriers had a higher chance to be responder to chemotherapy (adjusted odd ratio = 2.77; 95% CI: 1.83–4.18; adjusted < 0.001). The 6007C > T polymorphisms and BMP-4 expression also affect the prognosis of NSCLC. Patients with high BMP-4 expression had a significantly higher chance to be resistant to chemotherapy than those with low BMP-4 expression (OR = 2.81; 95% CI: 1.23–6.44; P = 0.01 ). The hazard ratio (HR) for 6007TT was 2.37 times higher than 6007CC (P = 0.003 ). In summary, the 6007C > T polymorphism of BMP-4 gene and BMP-4 tissue expression may be used as potential predictor for the chemotherapy response and prognosis of advanced NSCLC.